A New Small Satellite Sunspot Triggering Recurrent Standard and Blowout Coronal Jets - Miao, Yu Hu; Liu, Yu; Shen, Yuan Deng; Elmhamdi, Abouazza; Kordi, Ayman S.; Li, Hong Bo; Abidin, Zamri Zainal; Tian, Zhan Jun (American Astronomical Society, 2019)
In this paper, we report a detailed analysis of recurrent jets originated from a location with emerging, canceling, and converging negative magnetic field at the east edge of NOAA active region AR11166 from 2011 March 9 to 10. The event presented several interesting features. First, a satellite sunspot appeared and collided with a pre-existing opposite polarity magnetic field and caused a recurrent solar jet event. Second, the evolution of the jets showed blowout-like nature and standard characteristics. Third, the satellite sunspot exhibited a motion toward the southeast of AR11166 and merged with the emerging flux near the opposite polarity sunspot penumbra, which afterward, due to flux convergence and cancellation episodes, caused recurrent jets. Fourth, three of the blowout jets associated with coronal mass ejections (CMEs), were observed from the field of view of the Solar Terrestrial Relations Observatory. Fifth, almost all the blowout jet eruptions were accompanied with flares or with more intense brightening in the jet base region, while almost standard jets did not manifest such obvious features during eruptions. The most important feature, the blowout jets, were inclined to faster and larger scales than the standard jets. The standard jets instead were inclined to be relatively longer-lasting. The obvious shearing and twisting motions of the magnetic field may be interpreted as due to the shearing and twisting motions for a blowout jet eruption. The statistical results show that ∼30% of the blowout jets directly developed into CMEs. This suggests that the blowout jets and CMEs should have a close relationship. © 2019. The American Astronomical Society. All rights reserved.